Do the previous crop and top-dressing nitrogen fertilization change the yield and physiological and sanitary quality of common bean seeds? - da Cunha-Chiamolera, Tatiana Pagan Loeiro [UNESP]; Lemos, Leandro Borges [UNESP]; Coelho, Anderson Prates [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP] (FapUNIFESP (SciELO), 2022)
The aim was to evaluate the effects of previous crop and top-dressing nitrogen fertilization on the yield and physiological and sanitary quality of common bean seeds. The design used was in randomized blocks in a split-plot scheme, with four replications. The plots were represented by three previous crops (sole maize, maize + Urochloa ruziziensis and sole U. ruziziensis), preceding common bean. The subplots consisted of N doses (urea) applied as top-dressing (0, 40, 80, 120 and 160 kg N.ha-1) when the common bean had four expanded leaves. Physiological quality and sanitary quality of the seeds were evaluated through germination tests, first count, emergence speed index, accelerated aging, seedling emergence in the field and pathogen incidence, in addition to crude protein content, 100-seed weight and yield. The study factors did not interfere in the sanitary quality of the seeds. Under U. ruziziensis straw, the highest seed yield was obtained with the N dose of 115 kg.ha-1, while under sole maize and intercropping straw, the increase in yield was linear. Previous crop with U. ruziziensis, whether cultivated as sole crop or intercropped with maize, promotes greater physiological quality of common bean seeds, while top-dressing nitrogen fertilization does not interfere with quality, weight and protein content of the seeds.
Keywords: intercropped maize; Phaseolus vulgaris L; seed vigor; Urochloa ruziziensis; Zea mays L